'Signal integrity' in the Audiovisual Media Services Directive: Process, positions and policies examined and explained. (1st November 2021) - Afilipoaie, Adelaida; Dewaele, Steven; Donders, Karen
Technological convergence has pushed the broadcasting value chain into a state of imbalance. The updated Audiovisual Media Services Directive with its provision on signal integrity attempts to recalibrate the power relations in the value chain while also aspiring to achieve cultural objectives. By triangulating qualitative research methods, we investigate what signal integrity is from a legal and technical perspective, we identify the cases in which signals are protected and determine stakeholder positions. Our main finding is that signal integrity's scope might be larger than envisaged by the European Commission but needs to be more carefully pinned down to ensure consistency of definition, interpretation and application across Member States. Furthermore, while protecting signal integrity supposedly serves a combined economic and cultural agenda, it mainly serves broadcasters' financial interests. However, since broadcasters invest most in general interest and original content, this kind of economic protectionism could be justifiable.